Synthesis of Black-TiO2 and manganese-doped TiO2 nanoparticles and their comparative performance evaluation for photocatalytic removal of phenolic compounds from agro-industrial effluent - Nawaz, R. (Springer Science and Business Media B.V., 2021)
In this paper, the synthesis, characterization, and comparative performance of Black-TiO2 and manganese-doped TiO2 (Mn-TiO2) nanoparticles for photocatalytic removal of phenolic compounds from agro-industrial effluent known as treated palm oil mill effluent (TPOME) are reported. The Black-TiO2 nanoparticles were synthesized via a green synthesis approach using a renewable chemical, glycerol as a reducing agent. The Mn-TiO2 nanoparticles were synthesized via the wet impregnation method using potassium permanganate (KMnO4) as a precursor. Experimental results revealed that both types of TiO2 nanoparticles, Black-TiO2 and Mn-TiO2 nanoparticles were anatase phase with a particle size range from 30â80 nm, improved visible light absorption and narrow bandgap of 2.96 and 2.12 eV, respectively. The improved visible light absorption was ascribed to the presence of Ti3+ defect states in Black-TiO2 nanoparticles and the substation of Mn into TiO2 matrix in Mn-TiO2 nanoparticles. The improved visible light absorption led to the enhanced photocatalytic performance of Black-TiO2 and Mn-TiO2 nanoparticles. The former was able to remove 48.17 whereas the latter removed 39.11 of 224.85 mg/L of phenolic compounds from TPOME under 180 min of visible light irradiation. The Black-TiO2 and Mn-TiO2 nanoparticles showed 2.2-fold and 1.7-fold higher performance, respectively, than the Pure-TiO2 nanoparticles. The Black-TiO2 nanoparticles exhibited superior photocatalytic performance, and the highest reaction rate constant (Kapp = 0.31127) was achieved which is two-fold higher than the one obtained by Pure-TiO2 nanoparticles (Kapp = 0.14733). The recyclability test showed that Mn-TiO2 nanoparticles were more stable indicated by their negligible loss (1.55) of photoactivity after five repeated cycles. Â© 2021, The Author(s), under exclusive licence to Springer Nature B.V.